Sociological analysis of socio-cultural factors affecting social isolation: Case study of Bagh-e Bahadoran city - A. Ghorbani; N. Ounagh; A. Salehi (Taḥqīqāt-i Farhangī-i Īrān)
Youths are valuable assets of the society who would determine the future of that society. As a matter of fact, identifying different dimensions and factors affecting young people as well as finding solution to their problems are of great importance. The aim of this study, as the title indicates, is to sociologically analyze the effect of socio-cultural factors affective on social isolation with a case study of the city of Bagh-e Bahadoran. The research is descriptive and survey-based; with the statistical population being youths aged 17-25 years from that city. The statistical population included 2000 people, 322 of them were selected by the proportional sampling method. The theoretic framework of this research was based on viewpoints of different thinkers such as Durkheim, Hari Alper, Merton, Simmel, Almond, Paul, Inglehart, Gwen, Giddens, and Marcuse. Findings show that there is a direct relationship between religiosity, social participation and social isolation but they are not meaningful and thus the hypothesis is rejected. With respect to socio-economic base and social isolation, there is an inverse and meaningful relationship. A direct and significant relationship is also shown between social media viewing and social isolation. Also, there is a significant relationship between socio-economic base and the ratio of social media viewing with social isolation. The regression analysis results show that two independent and dependent variables are attached to a good model and are able to explain social isolation. Similarly, they found to provide a suitable fit in the modeling of media structural equations and socio-economic base. As a result, socio-cultural factors explain social isolation.